Answer: [tex]t_{n}[/tex] = 10n - 111
Step-by-step explanation:
The first term of the sequence is - 101
we need to confirm that the sequence is arithmetic , that is , if it is arithmetic , it must have a common difference (d).
d = second term - first term = third term - second term
d = -91 - (-101)
d = -91 + 101
d = 10
Therefore the formula for the nth term is given as:
[tex]t_{n}[/tex]= a + (n - 1 ) d
[tex]t_{n}[/tex] = - 101 + (n - 1) 10
[tex]t_{n}[/tex] = - 101 + 10n - 10
[tex]t_{n}[/tex] = -111 + 10n
Therefore :
[tex]t_{n}[/tex] = 10n - 111